Human subjective homologues of established basic emotion correlations in lower mammals: a neuro-psychoanalytic study - Pantelis, Eleni (Department of Psychology, 2020)
Early separation experiences predispose people to depression and depressive episodes are triggered by experiences of social loss. The normal separation response entails a 'protest' phase followed by a 'despair' phase. The affective neuroscience paradigm of Jaak Panksepp identifies two basic emotion systems as being centrally involved in this normal separation response, namely, PANIC/GRIEF and SEEKING, and it conceptualises the despair phase of the cascade as the normal prototype for depression. In affective terms, major depression is seen as a disorder characterised by an overactive PANIC/GRIEF system and an underactive SEEKING system. There is considerable pre-clinical research that underwrites this conclusion, but the evidence in humans is limited. The general aim of this thesis was to investigate the claim that the feelings associated with depression represent an abnormal variant of the normal mammalian separation response in human subjects. The PANIC/GRIEF and SEEKING systems were artificially stimulated and dampened in a sample of healthy volunteers (N=16) via the administration of opioid and dopamine antagonists and agonists. This was an exploratory study, with a double-blind, placebo-controlled, repeated-measures design. The effects of the medications on SEEKING, PANIC/GRIEF, positive and negative affect and mood were investigated using both quantitative and qualitative measures. The results provided suggestive rather than strongly confirmatory evidence for the central hypotheses of this study. Naltrexone (a mu-opioid antagonist) did not increase PANIC/GRIEF and negative affect as predicted but there was some evidence that it led to the worsening of mood, a significant reduction in positive affect and feelings of social and affective disconnection. Morphine (a mu-opioid agonist) reduced PANIC/GRIEF as predicted, but contrary to predictions, positive affect was reduced. There was some evidence to show that Morphine led to an increase in the expression of feelings of contentment, relaxation, happiness and reduced concern. Haloperidol (a dopamine antagonist) reduced SEEKING as predicted but did not increase negative affect as expected. There was some evidence to show that it led to a worsening of mood and positive affect and produced depressive affects such as low drive,low energy, loss of motivation and interest. Madopar (a dopamine agonist) did not increase SEEKING or improve mood as predicted, but there was some evidence that it generated positive affects and reduced the sadness associated with experiences of loss. On Haloperidol, participants with lower 'despair’ had significantly reduced SEEKING and positive affect and higher depression scores, compared to participants with higher 'despair’. On Madopar, participants with lower 'despair’ experienced a greater improvement in positive affect and mood, compared to those with higher 'despair’. On Morphine, measures of avoidant attachment rather than anxious attachment were comparatively more effective in differentiating between Low and High 'protest’, and that those with higher 'protest’ experienced comparatively more PANIC GRIEF, negative and depressive affect. These results provide some 'proof of concept’ for the conceptualization of depression as pathological 'despair’ and that depression feels bad because a dampened SEEKING system and a stimulated PANIC/GRIEF system produce the type of feelings that are characteristic of depression. The results also draw attention to factors that potentially contribute to the limited success of purely drug-focused interventions in depression.